From game to spectacle: the mediatization of streaming games on Twitch platform - Jéssica Galdino, Renata (2021)
This work analyzes the Twitch streaming platform from the perspective of mediatization, a process that conceives the phenomenon of new interaction patterns promoted by the media in their relationship with society. It is understood that the platform brings new experiences to user in the world of games, promoting interference in the original relation, such as watching, narrating or entering yourself as an influential figure, allowing the arising of new celebrities in the society of the spectacle.